Case report: A case of anti-recoverin antibody-positive encephalitis exhibiting Cotard and Capgras delusions that was successfully treated with electroconvulsive therapy - Akahane, Takaki; Takahashi, Naomi; Kobayashi, Ryota; Nomura, Konoka; Akiho, Masakazu; Shikama, Yukihiro; Noto, Keisuke; Suzuki, Akihito (Frontiers in Psychiatry, 2024)
Recoverin is a neuron-specific calcium-binding protein that is mainly located in the retina and pineal gland. Few reports have described patients with anti-recoverin antibody-positive encephalitis, and no cases of psychosis associated with this encephalitis have been reported. We report a patient with anti-recoverin antibody-positive encephalitis with Cotard and Capgras delusions who was successfully treated with electroconvulsive therapy (ECT). The patient was a 25-year-old woman. She exhibited disorientation, executive function deficits, tremors in the upper limbs, generalized athetoid-like involuntary movements, hallucinations, incontinence, and fever, which led to her admission to our hospital. Upon admission, she complained of Cotard delusions. Various diagnostic tests, including cerebrospinal fluid analysis, antibody screening, and brain imaging, were unremarkable, except for positivity for serum anti-recoverin antibodies, non-specific general slowing on electroencephalography and decreased regional cerebral blood flow (rCBF) in the frontal and occipital lobes, and increased rCBF in the basal ganglia and pons on single-photon emission computed tomography. She was eventually diagnosed with encephalitis positive for anti-recoverin antibodies and treated with immunoglobulins and steroids. Her neurological symptoms improved temporarily, but three months later, psychiatric symptoms, i.e., suicidal thoughts and Cotard and Capgras delusions, were exaggerated. After ECT, her condition significantly improved. In conclusion, the present report suggests that pineal gland dysfunction due to anti-recoverin antibody or its cross-reactivity with neuron-specific calcium-binding proteins may contribute to the neuropsychiatric symptoms observed in anti-recoverin antibody-positive encephalitis and that ECT can be a viable treatment option if immunotherapy proves ineffective. Additionally, decreased rCBF in the prefrontal cortex may be associated with the clinical features of Capgras and Cotard delusions.